Which risk factors are really predictive?: an analysis of Andrews and Bonta’s "Central Eight" risk factors for recidivism in German youth correctional facility inmates - Grieger, Lena (Criminal justice and behavior, 2014)
In this study, we examined the (incremental) predictive validity of Andrews and Bonta's Central Eight risk factors for recidivism in the German youth correctional system. The sample consisted of N = 589 male youth inmates who were incarcerated for the first time. Recidivism during the 78 months? follow-up was assessed using official data. The Central Eight risk factors predicted recidivism in survival analyses. In a cross-validation, composite scores predicted general (area under curve [AUC] = .65) and violent recidivism (AUC = .66). The Moderate Four risk factors (family, school, leisure/recreation, substance abuse) showed predictive validity incremental to the Big Four risk factors (history of antisocial behavior, antisocial personality pattern, antisocial cognition, antisocial associates). School was the most predictive single risk factor. The results provide evidence for the applicability of the Central Eight as predictors for recidivism in the German youth correctional system. Furthermore, the study adds to the debate on the importance of dynamic risk factors.